Single-particle tracking for DNA tether length monitoring - Pouget, Noëlle (Oxford University Press, 2004)
We describe a simple single-particle tracking approach for monitoring the length of DNA molecules in tethered particle motion experiments. In this method, the trajectory of a submicroscopic bead tethered by a DNA molecule to a glass surface is determined by videomicroscopy coupled to image analysis. The amplitude of motion of the bead is measured by the standard deviation of the distribution of successive positions of the bead in a given time interval. We were able to describe theoretically the variation of the equilibrium value of the amplitude of the bead motion with the DNA tether length for the entire applicable DNA length range (up to ∼3500 bp). The sensitivity of the approach was illustrated by the evidence obtained for conformational changes introduced into a Holliday junction by the binding of the Escherichia coli RuvA protein. An advantage of this method is that the trajectory of the tethered bead, rather than its averaged motion, is measured, allowing analysis of the conformational dynamics of DNA chains at the single-molecule level.